Heart rate mean and variability as a biomarker for phenotypic variation in preschoolers with autism spectrum disorder. Issue 1 (16th August 2018) - Bazelmans, Tessel; Jones, Emily J. H.; Ghods, Sheila; Corrigan, Sarah; Toth, Karen; Charman, Tony; Webb, Sara J.
Abstract : Interest in autonomic arousal in autism spectrum disorder (ASD) is increasing; however, reliability of these measures in ASD is unknown, and previously reported associations with social and cognitive abilities are inconsistent. This study assesses heart rate (HR) and HR variability (HRV) in preschoolers with ASD or typical development (TD) while they passively watched naturalistic videos. Measurement reliability, group differences, and the relationship with social and cognitive abilities were evaluated. Seventy one ASD and 66 TD children (2–4 years) provided cardiac data from two sessions. Test–retest intraclass correlations of HR and HRV over a 3‐week period were moderate to good in both groups. Groups did not differ in mean level of HR or HRV. Intra‐individual variability of HR between video segments within a session was higher in the ASD group, but intraclass correlations of this metric were low. Higher HR related to better language skills in TD children, but not after accounting for age and nonverbal ability. Higher HRV related to better expressive and receptive language in ASD children after controlling for age and nonverbal ability. HR/HRV were not related to social or executive functioning skills and did not explain any additional variance in abilities at a 12‐month follow‐up visit. In summary, variation in language abilities is associated with HR in the TD group and HRV in the ASD group. While preliminary, these results are promising for consideration of autonomic control as a biomarker for individual differences in ASD and may help us understand the mechanisms that contribute to communication skills. Autism Research 2019, 12: 39–52 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Cardiac activity, such as heart rate and heart rate variability, is linked to a wide range of psychological functions. This study shows that there is an association between heart rate and heart rate variability and language skills in young children with autism spectrum disorder (ASD). These results may help us understand what underlies individual differences in developmental abilities in young children with ASD.